Signaki as a Spiritual Heritage and Its Translation - З., Шадкам; А., Сүлейменова (Journal of Oriental Studies, 2019)
The research of ancient historical texts, rare books and written monuments is very important nowadays. It is known that many manuscripts, historical texts and rare books have not reached to the researchers for different reasons. One of the manuscript that has not been scientifically researched is the genealogy of Sygnaki. The genealogical manuscript was written In Central Asia, in the South part of the modern Kazakhstan. In this manuscript we can see the names of people, historical and religious figures and names of geography places. Our purpose in researching this work is to find the person and geographical names and explain the relationship between them. However, we can not do all the research we have here. Our main goal is to find out the languages in which manuscript written, research when and where they were written, to specify of the Persian, Arabic and Turkic words in the text, to find the names of the historical and religious figures, the name of the place and the geographycal names. e hope that this achievement will be a form of research for historians, journalists, ethnographers and researchers. Key words: of Signaki, manuscript, spiritual heritage.